The Impact of Memory Effects on Lymphatic Filariasis Transmission Using Incidence Data From Ghana - Fredrick A. Wireko; Rebecca Awerigiya; Isaac K. Adu; Joshua N. Martey; Bernard O. Bainson; Joshua Kiddy K. Asamoah (Engineering Reports, 2025)
ABSTRACT Lymphatic filariasis is a neglected tropical disease caused by a parasitic worm transmitted to humans by a mosquito bite. In this study, a mathematical model is developed using the Caputo fractional operator. The model also examined the influence of the rate of awareness of the disease and the mass administration of drugs on their contribution to mitigating the spread of the disease during an outbreak. We compared the model with lymphatic filariasis‐infected cases in Ghana from 2010 to 2021. Using the Hyers‐Ulam and Hyers‐Ulam‐Rassias stability criterion, we theoretically showed that the proposed model is stable. The basic reproduction number calculated based on the parameters obtained is ℛ0=1.5746 with a normalized mean square error of 0.0198. Through sensitivity index analysis and numerical simulations, we noticed that the mosquito bite rate β directly contributes to the spread of the disease. In contrast, the rate of awareness of the disease will help mitigate the spread of the disease during an outbreak.